Sustainable Human Resource Practices and Framework in the Selected Philippine State Universities and Colleges (SUCs): A Case Study - Ryan Mark Ambong; John Eric Estrellado (Universidade Estadual de Alagoas, 2024)
Despite the significance of Sustainable Human Resource Management (SHRM), there is a dearth of academic literature on this subject in the context of Philippine State Universities and Colleges (SUCs). The goal of this research is to analyze current human resource practices, look at the key underlying factors that affect them, and develop a comprehensive and integrated model of human resource management that considers shifting social and economic conditions as well as the demographics of the workforce in SUCs. The proposed model can be used as a roadmap to enhance human resource practices, develop human capital, and create more sustainable human resource planning in the Philippine public sector. For this case study, information was gathered through in-depth interviews with 30 key respondents from selected SUCs who held managerial, supervisory, and rank-and-file positions. The study's findings will offer advice to academic HR managers on how to improve HR procedures and administration to be more employee-focused. Thus, the proposed framework is useful for making decisions about how to sustain employees in the Philippine SUCs.